Reserva de Hemoderivados Preoperatorios en pacientes sometidos a cirugía electiva en el Hospital Universitario Nacional. Implementación del modelo MSBOS (Maximum Surgical Blood Order Schedule) (2020)
The use of blood products is a frequent therapy in the perioperative period, mainly when the patient faces a loss of blood related to the surgical intervention that can compromise his life. Anticipating these possible complications is part of the pre-surgical evaluation performed by the anesthesiologist and the surgeon, and preventive measures must be taken to dispose of the necessary supplies if required, which corresponds to the reserve of blood products. However, it is an intervention that carries additional costs in health care and is not without multiple risks, so it is necessary to have clarity in which patients and in which surgical interventions they benefit from having the red blood cell reserve. Different guidelines have been developed to improve the use of blood in the perioperative period, such as the maximum request for surgery (Maximum Surgical Blood Order Schedule), which consists of a list of surgical interventions and the maximum number of blood units that they require cross-compatibility tests for each intervention and thus reduce the request for unnecessary reservations. Given that it is difficult to extrapolate current practices with institutions in other places due to differences in the classification of surgical procedures, differences in populations, combination of elective and emergency procedures as well as the surgical experience of each care center, the application of MSBOS scheme must be developed by each hospital in charge of blood providers and users. The main objective of our study was to improve the effectiveness of the arrangement and use of blood and blood products by formulating MSBOS for common procedures, in order to provide the required compatible units in a few minutes and decrease the reservation request and unnecessary cross-testing, which will impact the quality of care, improvement in blood bank monitoring indicators and cost reduction.